PENGARUH FAKTOR LINGKUNGAN TERHADAP POLA PENYEBARAN MOLUSKA PADA EKOSISTEM MANGROVE ALAMI DAN HASIL REHABILITASI - Andi Nur Samsi; Sharifuddin Bin Andy Omar; Andi Niartiningsih (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2018)
Mangrove ecosystem is a habitat of Molluscs (Gastropoda and Bivalvia). This ecosystem is always influenced by environmental factors. This study aims to determine the influence of environmental factors on the distribution patterns Molluscs of natural mangrove ecosystems in Pannikiang Island, Barru Regency and rehabilitation mangrove ecosystem in Tongke-tongke village, Sinjai regency. This research uses the quantitative method. Environmental factors measured were temperature and salinity of the water, aswell as carbon and nitrogen content of sediment. Samples of Molluscs (Gastropoda andBivalves) and sediments were taken randomly. The observations of the Molluscan community include the composition of Mollusc species (Gastropoda and Bivalvia) anddispersal patterns. Data were analyzed by using multiple linear regression. The results showed that the distribution pattern of Molluscs (Gastropoda and Bivalvia) at both sites was not significantly different and the temperature, salinity, carbon, and nitrogen sediments also did not affect the Mollusk distribution pattern in both sites.